2013
DOI: 10.1016/j.ypmed.2013.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Reducing sitting time in office workers: Short-term efficacy of a multicomponent intervention

Abstract: This multicomponent workplace intervention demonstrated that substantial reductions in sitting time are achievable in an office setting. Larger studies with longer timeframes are needed to assess sustainability of these changes, as well as their potential longer-term impacts on health and work-related outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
443
9
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 315 publications
(485 citation statements)
references
References 34 publications
27
443
9
6
Order By: Relevance
“…4-12 weeks) effectiveness for reducing occupational sitting by providing workers with sit-tostand work desks, 36-38 a combined approach of installing sit-to-stand work desks and providing support at a management/ organisational level, 37 or specifically designed computer prompting software to reduce workplace sitting. 39,40 However, at present, the long-term effectiveness in reducing sitting time and the effects on health outcomes of such interventions remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…4-12 weeks) effectiveness for reducing occupational sitting by providing workers with sit-tostand work desks, 36-38 a combined approach of installing sit-to-stand work desks and providing support at a management/ organisational level, 37 or specifically designed computer prompting software to reduce workplace sitting. 39,40 However, at present, the long-term effectiveness in reducing sitting time and the effects on health outcomes of such interventions remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…One trial reported successful reductions in sitting time by 125 minutes/day over 4 weeks [89], while two longer 12 week randomised controlled trials reduced sitting time 94 minutes/day [90], and 58.7 minutes/day [91] respectively, with reductions in waist circumference compared to a control condition.…”
Section: An Ecological Perspective On Changing Sedentary Behavioursmentioning
confidence: 99%
“…When examining individual changes, 87.5 % of participants reduced sedentary time and increased light-intensity physical activity. Several other trials have demonstrated promise in reducing sedentary time among office workers using various interventions that include computer software [26], computer software and text messages [30], sit-stand workstations [23,31], portable pedal bike [24], or an in-person session [32]. Furthermore, the magnitude of changes in sedentary time and light activity in the current trial (sedentary change, −8.1 %; light activity change, 7.9 %) were slightly larger than those seen in a recent trial by Bond et al [33] that used similar technology to interrupt sedentary time (sedentary change, -3.3 to −5.9 %; light activity change, 2.7 to 4.7 %).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have sought to reduce total or leisure sedentary time [22][23][24][25]; however, few have examined breaking up sedentary bouts [26]. Evans et al [26] examined the use of computer software that encourages individuals to stand up every 30 min, but differences in total sedentary time were not observed between the intervention and control groups.…”
Section: Introductionmentioning
confidence: 99%